Intersections of behavior analysis with cognitive models of contingency detection - Cigales, Maricel (1997)
Bower and Watson have offered, respectively, a logical hypothesis-testing model and a conditional probability model of contingency detection by young infants. Although each could represent cognitive processes concomitant with operant learning, empirical support for these models is sparse. The limitations of each model are discussed, and suggestions are made for a more parsimonious approach by focusing on the areas of overlap between the two.